2005
DOI: 10.1074/jbc.m504828200
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular Matrix and Inflammation

Abstract: Components that propagate inflammation in joint disease may be derived from cartilage since the inflammation resolves after joint replacement. We found that the cartilage component fibromodulin has the ability to activate an inflammatory cascade, i.e. complement. Fibromodulin and immunoglobulins cause comparable deposition of C1q, C4b, and C3b from human serum. Using C1q and factor B-deficient sera in combination with varying contents of metal ions, we established that fibromodulin activates both the classical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 156 publications
(50 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…It was previously reported that FMOD binds C1q, which leads to complement activation (21). FMOD also binds FH, causing inhibition of the alternative pathway and thus a decrease in membrane attack complex formation (21). In the latter case, it is not clear which parts of the two molecules are involved in the interaction, although binding to C1q and FH, respectively, appears to engage different sites on FMOD.…”
Section: The Tyr-384 Variant Of Fh Interacts With Fmod With Higher Afmentioning
confidence: 83%
See 3 more Smart Citations
“…It was previously reported that FMOD binds C1q, which leads to complement activation (21). FMOD also binds FH, causing inhibition of the alternative pathway and thus a decrease in membrane attack complex formation (21). In the latter case, it is not clear which parts of the two molecules are involved in the interaction, although binding to C1q and FH, respectively, appears to engage different sites on FMOD.…”
Section: The Tyr-384 Variant Of Fh Interacts With Fmod With Higher Afmentioning
confidence: 83%
“…Phosphorylcholine-bovine serum albumin (PC-BSA) was prepared by coupling p-aminophenyl-phosphorylcholine to bovine serum albumin according to the procedure described by Padilla et al (26). Deglycosylated FMOD was prepared by treatment with N-glycosidase F (Roche Applied Science) as previously described (21).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large body of evidence shows that complement contributes to the development of RA in man and experimental animals (5). It has been shown that fibromodulin (FM) and osteoadherin (OSAD), constituents of the extracellular matrix, activate complement via the classical pathway and may enhance inflammation in joint disease (6,7). Fragments of these cartilage components are released by proteases during cartilage destruction to come in contact with complement in synovial fluid.…”
mentioning
confidence: 99%